Personality traits across the life cycle: Disentangling age, period, and cohort effects - Bernd Fitzenberger; Gary Mena; Jan Sebastian Nimczik; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Despite the importance for socio-economic outcomes, there is an ongoing debate about the stability of personality traits over the life cycle. By disentangling age, period and cohort influences on personality traits, this paper adds to the existing empirical contributions, which often focus on age patterns and disregard cohort and period influences. We present the results from systematic specification tests that provide novel evidence for the separability of age, period, and cohort effects in almost all personality traits. Our estimates also document that for different cohorts, the evolution of personality traits across the life-cycle follows a stable, though non-constant, age-profile, while there are sizeable differences across time periods
Keywords: D8; J1; 330; Big Five personality traits; Locus of Control; Risk attitudes; age-periodcohort decomposition; life cycle